Gene-environment interactions in Autism Spectrum Disorder - Santos, João Pedro (2018)
Autism Spectrum Disorder (ASD) is a heterogeneous neurodevelopmental disorder characterized by deficits on social communication and interaction and repetitive and stereotyped behaviors. ASD heritability is estimated at 50%, with multiple rare genetic variants, including Copy Number Variants (CNVs), implicated in its etiology. This suggests a role of non-genetic factors in modulation of ASD risk, including pre-, peri- and post-natal exposure to environmental toxicants. We thus hypothesize that ASD is the result of the interaction of a genetic susceptibility with exposure to environmental factors. Here we tested whether affected individuals have an excess of CNVs targeting genes involved in detoxification of xenobiotics or regulation of barriers permeability (blood-brain barrier, placenta and respiratory cilia). CNVs were analyzed in 2446 children with ASD recruited through the Autism Genome Project (AGP)[1]. Deletions and duplications were compared with control individuals from the Database of Genomic Variants (N=9649), and inheritance status was assessed. Results were validated using the Simons Simplex Collection (SSC). Resorting to The Comparative Toxicogenomics Database (CTD) we explored interactions between the studied genes and environmental factors. Through literature and database review we identified 519 relevant detoxification and barrier genes. CNVs targeted 173 (33.3%) of these genes in 555 (22.7%) ASD subjects from the AGP dataset. 31 of these genes were exclusively targeted by CNVs in ASD patients, while 24 genes were more frequently targeted by CNVs in ASD patients compared to controls, after Bonferroni correction (P<4.587x10-4). 8 of the 31 (25.8%) genes targeted exclusively in AGP-subjects and 7 of the 23 (30.4%) genes more-frequently targeted in AGP-subjects were validated upon analysis of the SSC dataset. Among the identified genes are members of UGT, CYP450, SLC, GST and ABC families. An exploratory analysis demonstrated that most of these genes interact with environmental toxicants associated with ASD, such as bisphenol A, heavy metals. polycyclic aromatic hydrocarbons, pesticides and phthalates. This study reinforces the hypothesis that the exposure to environmental factors in genetically susceptible individuals contributes to ASD risk. Prospectively, we will measure the levels of specific toxicants in biological matrices (i.e. blood, urine and naturally-shed deciduous teeth) collected from Portuguese children with a diagnosis of ASD and correlate these parameters with genetic and clinical data.